2020
DOI: 10.1016/j.ijpsycho.2019.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Personality, cardiovascular, and cortisol reactions to acute psychological stress in the Midlife in the United States (MIDUS) study

Abstract: Recent research has suggested that diminished, as well as elevated reactivity to acute psychological stress is maladaptive. These differences in stress reactions have been hypothesised to relate to the Big Five personality traits, which are said to be biologicallybased and stable across adulthood; however, findings have been inconclusive. This study sought to replicate the findings of the largest study conducted to date (Bibbey, Carroll, Roseboom, Phillips, and de Rooij, 2013), with a sample of participants fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 42 publications
(54 reference statements)
1
19
1
Order By: Relevance
“…The study results showed that lower cortisol, heart rate, systolic and diastolic blood pressure were found in individuals with higher neuroticism when reacting to psychological stressors. Coyle et al (2020) replicated the described study and found that neuroticism was negatively related to cortisol reactivity. Moreover, Poppelaars, Klackl, Pletzer, Wilhelm, and Jonas (2019) found that higher neuroticism predicted lower sympathetic nervous system reactivity at the time of exposure to a psychological stressor.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…The study results showed that lower cortisol, heart rate, systolic and diastolic blood pressure were found in individuals with higher neuroticism when reacting to psychological stressors. Coyle et al (2020) replicated the described study and found that neuroticism was negatively related to cortisol reactivity. Moreover, Poppelaars, Klackl, Pletzer, Wilhelm, and Jonas (2019) found that higher neuroticism predicted lower sympathetic nervous system reactivity at the time of exposure to a psychological stressor.…”
Section: Introductionsupporting
confidence: 77%
“…Stress-moderation models indicate that personality can impact the biological stress response system (Hutchinson & Ruiz, 2011). Numerous studies highlight that neuroticism has the strongest relation to stress than other Big Five traits (Coyle, Howard, Bibbey, Gallagher, Whittaker & Creaven, 2020). Even the research results of the relationship between acute stress and neuroticism are controversial, yet mostly confirmed is this trait relation to higher emotional stress reactivity (Suls & Martin, 2005), but lower cortisol and cardiovascular stress reactivity (Bibbey et al, 2013;Coyle et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This includes analysis of publicly available datasets (quantitative or qualitative), data already collected by the supervisor, or by the student prior to the dissertation (e.g., as part of a research assistantship). For example, for a master's dissertation (Coyle et al, 2020), AMC and colleagues conducted a conceptual replication of a study of associations between personality and stress reactivity (Bibbey et al, 2013) using publicly available data from the Midlife in the United States study.…”
Section: Secondary Data Analysismentioning
confidence: 99%
“…Although publications using the data are not a substitute for technical documentation (and may contain errors), students may find them useful. Replication studies may also be feasible (e.g., Coyle et al, 2020). The advantages of replication for learning and guidance on choosing what to replicate for teaching purposes are discussed in-depth elsewhere (see Janz, 2016).…”
Section: Considerations and Implementationmentioning
confidence: 99%
“…This model reduces personality to five traits: extroversion, open-mindedness, amiability, conscientiousness and neuroticism [15,67,68]. Some studies have tried to understand if and which personality traits can be considered predictors of stress [64,[69][70][71][72][73][74].…”
Section: Introductionmentioning
confidence: 99%